Respuesta :

Answer:

x = - 3 and x = - 4

Step-by-step explanation:

(a)

The denominator of f(x) cannot be zero as this would make f(x) undefined. Equating the denominator to zero and solving gives the value that x cannot be.

solve x + 3 = 0 ⇒ x = - 3

(b)

Equate f(x) to 5, that is

[tex]\frac{2x+3}{x+3}[/tex] = 5 ( cross- multiply )

5(x + 3) = 2x + 3 ( distribute left side )

5x + 15 = 2x + 3 ( subtract 2x from both sides )

3x + 15 = 3 ( subtract 15 from both sides )

3x = - 12 ( divide both sides by 3 )

x = - 4



ACCESS MORE